Proceedings of the 5th Universitas Ahmad Dahlan Public Health Conference (UPHEC 2019) 2020
DOI: 10.2991/ahsr.k.200311.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infection of Endoparasites and Its Intensity in Small Mammals’ Liver Captured from Irrigated Rice Crop Area and Villages

Abstract: The research was conducted during November 2018 -January 2019 in two provinces namely West Java and Yogyakarta. The aim of the study was to study the prevalence of infection of endoparasites inhabiting the liver of small mammals and its intensity. Two different habitats, irrigated rice crop area and two villages closed each other were chosen as trapping sites. Sampling was conducted by performing two methods i.e. trapping using snap trap and LTBS (Linear Trap Barrier System) continually. The snap traps (75 pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…A continuous study in two provinces has revealed the presence of two helminth parasites in the livers of rodents and other small mammals captured in lowland rice irrigated areas and villages. In comparison to the rodent caught from the village habitat, the prevalence of infection here is higher [42].…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…A continuous study in two provinces has revealed the presence of two helminth parasites in the livers of rodents and other small mammals captured in lowland rice irrigated areas and villages. In comparison to the rodent caught from the village habitat, the prevalence of infection here is higher [42].…”
Section: Introductionmentioning
confidence: 59%
“…To attract the animals, a daily fresh bait of salty fish and roasted coconut was applied. These traps were monitored the next morning to observe for captured animals and to replace the bait with new ones [42]. Subsequently, all captured animals were then identified morphologically [1], sexed, and recorded for the biological attributes (body weight, tail length, head-body length, mammary formulae, foot, and ear length) before dissection (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations